Energy Spectrum of an Electron Beam Outputted into Ambient Air on an Electron Accelerator with a Grid Plasma Cathode; 20th International Symposium on High-Current Electronics (ISHCE) - Vorobjev (Vorobyov) M. S. Maksim Sergeevich; Tarasenko V. F. Victor Fedotovich; Baksht E. Kh.; Kozyrev A. V.; Koval N. N. Nikolay Nikolaevich; Doroshkevich S. Yu. (2018, 2018)
Title screen